The Experiences of Elementary Learners in the National Learning Camp (NLC) Program of DepEd, Division of Zambales, Philippines - Elbert D. Fronda; Marie Fe D. De Guzman; Leila L. Ravana (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study utilized a phenomenological research methodology to explore the lived experiences of elementary Grade 3 pupils in Zone 2, Division of Zambales, who participated in the National Learning Camp (NLC) program. Participants were selected via purposive sampling, ensuring they met specific criteria including: (1) was a bona fide grade 3 pupil participating in the NLC program; (2) had completed at least one full cycle of the NLC program; (3) whose parents/guardians had provided written informed consent for their participation in the study; and (4) was able to communicate their thoughts and experiences clearly and effectively. Qualitative data were gathered through in-depth semi-structured interviews and focus group discussions and subsequently analyzed using Bingham's five-phase thematic analysis. The findings show that the National Learning Camp successfully created a positive and engaging learning environment for pupils; and enriching experiences in reading and game-based activities. The participants described the challenges in terms of environmental, resources and pedagogical; and emotional struggles. Despite the identified challenges, pupils particularly valued the NLC's impact on basic literacy and their overall perception of learning, crediting to their supportive teachers for much of this success. To further enhance the program, pupils recommend strengthening foundational skills through engaging, hands-on activities, providing personalized attention, and optimizing program duration and resources.